Pengembangan model Community Water Quality Screening berbasis TDS meter dan PH meter untuk meningkatkan literasi masyarakat terhadap air layak konsumsi di Desa Bandar Baru - Zufri Hasrudy Siregar; Adinda Juita Nasution; Yuri Dwi Lianto; Syafrida Hanum; Refiza; Ilmi Abdullah; Riana Puspita; Arif Fadillah Nasution (Jurnal Derma Pengabdian Dosen Perguruan Tinggi (Jurnal DEPUTI), 2026)
Limited access to laboratory testing encourages communities to assess water mainly by clarity, odor, and taste. This approach cannot adequately detect changes in physicochemical characteristics. This community engagement program developed a Community Water Quality Screening model using TDS and pH meters in Bandar Baru Village. The model integrates education, calibration, duplicate measurements, restricted interpretation, risk communication, and laboratory referral. The analytical draft uses a structured simulated dataset of 48 participants and 72 water samples from six source types. Analyses included descriptive statistics, paired t tests, McNemar tests, Kruskal-Wallis tests, chi-square tests, Spearman correlations, intraclass correlation coefficients, and linear regression. Mean literacy scores increased from 42.0 to 70.6 out of 100, a mean increase of 28.5 points (95% CI 25.9-31.1; p<.001). 85.4% of participants mastered at least eight of ten procedural steps. Of 72 samples, 44 were classified as green, 22 as yellow, and 6 as red. Water source type was associated with screening category (chi-square=33.36; p<.001; Cramer V=0.48). Duplicate measurements showed very high consistency for pH (ICC=0.998) and TDS (ICC=1.000). The model offers a practical educational framework but does not replace microbiological and comprehensive chemical testing.